A South American bioinvasion case history: Limnoperna fortunei (Dunker, 1857), the golden mussel - Darrigran, Gustavo Alberto (2005)
Two factors combine in this age of globalization to favor the establishment of alien species in natural environments: human activities and global climate change. This paper reviews the recent invasion of the golden mussel, Limnoperna fortunei, in South America, including its impacts in natural and human environments. This case study allows the identification of the likely impacts that morphologically and functionally similar invasive species will have in similar environments, such as in North America, which is considered to be at high risk of invasion by L. fortunei.